Comparison of the impact of intermittent fasting diet alone or in conjunction with probiotic supplementation versus calorie-restricted diet on inflammatory, oxidative stress, and antioxidant capacity biomarkers in women with polycystic ovary syndrome: A randomized placebo-controlled trial - Sepide Talebi; Sakineh Shab-Bidar; Gholamreza Askari; Hamed Mohammadi; Ashraf Moini; Kurosh Djafarian (Journal of Research in Medical Sciences)
Background: The objective of this study was to compare the effects of early time-restricted eating (eTRE) and eTRE plus probiotic supplementation to daily caloric restriction (DCR) alone in terms of biomarkers of oxidative stress (OS), antioxidant capacity, inflammation, and blood pressure (BP) in obese women with polycystic ovary syndrome (PCOS). Materials and Methods: The research was conducted as a randomized, parallel, placebo-controlled clinical trial with an 8-week follow-up period. Participants were randomly assigned to one of three groups: 14:10 eTRE with probiotic supplementation (n = 30), 14:10 eTRE with placebo supplementation (n = 30), or DCR with placebo supplementation (n = 30). At the beginning and 8 weeks of the intervention, systolic blood pressure (SBP) and diastolic BP, inflammation, and OS parameters were evaluated. Results: A total of 90 participants (mean age, 30.49 years and mean weight, 81.45 kg) were enrolled in this trial. After 8-week intervention, we observed SBP significantly decreased in both the eTRE + probiotic group (−0.31 mmHg [95% confidence interval (CI): −0.55, −0.07]) and the eTRE + placebo group (−0.24 mmHg [95% CI: −0.43, 0.04]), with no significant differences observed between groups. Moreover, C-reactive protein (CRP) levels were significantly reduced in all groups (P < 0.005). Total antioxidant capacity (TAC) also showed notable improvement in both the eTRE + probiotic group (P = 0.012) and the DCR group (P = 0.032). However, there were no significant differences between the three groups regarding BP, OS, TAC, and CRP markers. Conclusion: It was not found that eTRE alone or eTRE with probiotics intervention resulted in improving BP, inflammatory, OS, and antioxidant capacity biomarkers than a standard DCR diet among obese women with PCOS. The present study did not reveal significant improvements in BP, inflammatory markers, OS, or antioxidant capacity with either eTRE alone or eTRE combined with probiotics compared to a standard DCR among obese women diagnosed with PCOS. Trial Register no: IRCT20121110011421N5.